Culture-related grief beliefs of Chinese Shidu parents: Development and psychometric properties of a new scale. Issue 1 (31st December 2019) - Shi, Guangyuan; Wen, Jun; Xu, Xin; Zhou, Ningning; Wang, Jiani; Shi, Yuqing; Liu, Han; Wang, Jianping; Stelzer, Eva-Maria
ABSTRACT: Background : In China, parents whose only-child dies and who have no living or adopted child are called Shidu parents. Negative thinking is assumed to contribute to the development of emotional problems in bereavement. Because grief cognitions are likely influenced by the concepts of Chinese traditional culture (e.g., family continuation), Shidu parents may hold specific culture-related grief beliefs about themselves or the world, which, in turn, could impede their recovery. Objective : This study developed a questionnaire assessing the culture-related grief beliefs of Shidu parents and examined its psychometric properties. Methods : This newly developed questionnaire was administered to the combined sample of 313 Shidu parents. Exploratory (n = 164) and confirmatory factor analysis (n = 149) were conducted. Psychometric properties of the questionnaire were evaluated. Results : Exploratory factor analysis revealed three distinct factors (filial piety belief, destiny belief and perceived stigma), generating a nine-item culture-related grief beliefs of Shidu parents questionnaire (CBSQ). Confirmatory factor analysis verified the three-factor structure (χ 2 (24) = 39.103, p = 0.027, χ 2 /df = 1.630, CFI = .980, TLI = .970, RMSEA = .065, SRMR = .052). Internal consistency and temporal stability were adequate. Convergent, discriminant and concurrent validity were supported. Conclusions : This study highlights the importance of extending the concept of grief cognitions to include culture-specific beliefs, and provides a first measurement tool to assess culture-related grief beliefs after only-child loss, which can be used in future research with Shidu parents. HIGHLIGHTS: In China, parents whose only-child dies are called Shidu parents. Negative cognitions are assumed to contribute to the development of emotional problems in bereavement. This study highlights the importance of extending the concept of grief cognitions to include culture-specific beliefs. If cognitive grief theories are correct in assuming a contribution of grief cognitions to the development of maladaptive grief response, modification of culture-related grief beliefs should promote adjustment to loss in Shidu parents. This study provides a first measurement tool to assess culture-related grief beliefs after only-child loss, which comprises the three dimensions filial piety belief, destiny belief and perceived stigma. These subscales reflect common culture-related beliefs experienced by Shidu after the loss of their only-child. The culture-related grief beliefs of Shidu parents questionnaire (CBSQ) has good reliability and validity in China and can be used for future Shidu research.